Kinerja Pelayanan Angkutan Bus Transjakarta Korioor Pulo Gadung-Harmoni - Noviyanti, Noviyanti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The Jakarta administration hopes the communihJ who currently use private vehicles as a means oftransportation will turn to the Trans Jakarta Bus as a means of transportation. It is felt not east),comfort becomes the main reason people who do not want to turn to this rrwde of transportation.Corridor 2 with Pulogadung route-Harrrwny is a rorridor with a very dense number of (JllSsengers.The position of the stop which is at Pulogadung termi.nal, and must come together with bus and othervehicles that serve the transportation lxJth within and outside the dty certai.nly un1l reduce the comfortof this transport service user. Related to the above, need to be evaluated against the performance.of service providers-Wm) bus transportation in this corridor.Keywords: Bus Way, Stop, Bus Rapid Transit